2012
DOI: 10.5402/2012/890820
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Walk-In Type Hemicylindrical Solar Tunnel Dryer for Industrial Use

Abstract: This paper deals with the critical design specifications and field performance of walk in type hemicylindrical solar tunnel dryer for drying 1500vkg industrial product (dibasic calcium phosphate) in actual use. A tunnel like framed structural covered with UV-stabilized polythene sheet walk-in type solar tunnel dryer was designed, developed, and commissioned at Udaipur (27∘ 42′  N, 75∘ 33′  E), Rajasthan, India with a solar collector area of 134.74 m2 for drying di-basic calcium phosphate, having an initial moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…in 8 h [17]. Critical design specifications and field performance of a walk-in type hemicircular solar tunnel dryer for drying 1500 kg of industrial products were reported by Seveda, Damena et al, and Qin et al [9,22,23].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…in 8 h [17]. Critical design specifications and field performance of a walk-in type hemicircular solar tunnel dryer for drying 1500 kg of industrial products were reported by Seveda, Damena et al, and Qin et al [9,22,23].…”
Section: Introductionmentioning
confidence: 93%
“…Understanding many physical and biological processes requires detailed information on the availability of solar radiation on the earth's surface [6][7][8]. In Ethiopia, solar energy is used for domestic and commercial water heating in major cities, as well as solar electricity for tele-communication stations, lighting systems for households, cooking, drying grains (traditionally), and water supply in rural areas, and even refrigerating medicine in health centers [9][10][11][12][13][14][15]. In most areas, the farmers or institutions grow fruit and vegetables that have to be sold in the market immediately after harvesting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within two days, the moisture content decreased from 62.87% to 10.62%. The performance of the solar dryer was evaluated under both no load and full load conditions [16]. Extensive literature surveys highlight the necessity and ample room for developing new designs to enhance the drying process across various fields, particularly in the context of drying food products.…”
Section: Introductionmentioning
confidence: 99%